2023
DOI: 10.3389/fmicb.2023.1266025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of rumen metagenome, metatranscriptome, fermentation and methane yield in cattle and buffaloes fed on the same diet

Pradeep K. Malik,
Shraddha Trivedi,
Atul P. Kolte
et al.

Abstract: A study to compare the rumen microbial community composition, functional potential of the microbiota, methane (CH4) yield, and rumen fermentation was conducted in adult male cattle and buffaloes fed on the same diet. A total of 41 phyla, 169 orders, 374 families, and 1,376 microbial genera were identified in the study. Bacteroidetes and Firmicutes were the two most dominant bacterial phyla in both cattle and buffaloes. However, there was no difference in the abundance of Bacteroidetes and Firmicutes in the rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 129 publications
6
3
0
Order By: Relevance
“…A comparable distribution of Bacteroidetes and Firmicutes and a similar F/B ratio in the present study led to a non-significant difference in the nutrient digestibility and VFA production between the cattle and buffaloes fed on a mixed diet consisting of equal proportions of dry and green roughages and concentrate. These findings are in good agreement with the recent reports [ 12 , 71 ]. However, a few reports revealed that buffaloes have a greater abundance of Firmicutes and Bacteroidetes than cattle [ 9 , 14 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…A comparable distribution of Bacteroidetes and Firmicutes and a similar F/B ratio in the present study led to a non-significant difference in the nutrient digestibility and VFA production between the cattle and buffaloes fed on a mixed diet consisting of equal proportions of dry and green roughages and concentrate. These findings are in good agreement with the recent reports [ 12 , 71 ]. However, a few reports revealed that buffaloes have a greater abundance of Firmicutes and Bacteroidetes than cattle [ 9 , 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…The identified rumen microbiota affiliated with 43 phyla, 86 classes, 200 orders, 458 families, and 1722 genera in this study were consistent with the previous reports in cattle [ 10 , 32 , 70 ] and buffaloes [ 56 , 71 ]. The dominance of Bacteroidetes and Firmicutes phyla in the rumen metagenome of cattle and buffaloes was in good agreement with the recent reports [ 12 , 56 , 63 , 72 ]. These two bacterial phyla are primarily involved in the degradation of complex polysaccharides and VFA production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Euryarchaeota are a class of archaea that encompasses most species within archaea and often includes methanogens found in animal intestines. In the cladogram, the abundances of Methanobacteria , Methanobacteriales , and Methanobacteriaceae significantly increased in the HBCS group, all of which are associated with methane production [ 27 ]. The primary function of these archaea is to generate methane using substrates obtained during rumen fermentation, an interesting phenomenon as increased methane production signifies a reduction in energy utilization efficiency, which leads to decreased energy for fat accumulation.…”
Section: Discussionmentioning
confidence: 99%